Generation of 1319 nm Pulsed Vortex Laser by Annular Pumped Bonded Nd:YAG/V:YAG Crystal - Sen Yue; Shanshan Cao; Wenbin Qin; Menghua Jiang; Youqiang Liu; Yinhua Cao; Zhiyong Wang (Photonics)
Vortex lasers have shown significant advantages in fields such as quantum communication and optical detection due to their unique optical field structure. In this manuscript, we present a watt-level nanosecond Laguerre–Gaussian vortex beam from an end-pumped bonded Nd:YAG/V:YAG laser, which was pumped by a ring-shaped beam shaped by an axicon focusing system. By solving the transfer matrix of the resonator and designing a corresponding pump beam shaping system, mode matching between the LG01 beam and the annular pump beam was effectively achieved. The conditions for exciting the LG01 mode were theoretically calculated, and experimental results verified that the pump power required to excite the LG01 vortex beam is approximately twice that for exciting the fundamental Gaussian mode. Stable output of nanosecond lasers in the LG01 mode was achieved, with an output power of 1.943 W, a highest repetition rate of 291.3 kHz, a pulse width of 3.3 ns, and beam quality factors of <semantics><msubsup>Mx2</msubsup>=2.17</semantics> in the horizontal direction and <semantics><msubsup>My2</msubsup>=2.21</semantics> in the vertical direction. The results have significant value for applications such as visible light communication and high-resolution laser imaging.